From Pizza Hut to Hazard: Some Authentic Materials to Motivate Students. - Ng, Judy Miang Koon (INTI Publishing House Sdn. Bhd., 2007)
Students are more motivated to participate in class activities when authentic materials are used. One benefit of using authentic materials is that they encourage students to be responsible for their own learning, while promoting learner-centeredness. Authentic materials are rich in cultural background. The learning of cultures is essential for students, especially as they communicate with others from various cultures and customs. The researcher has designed some worksheets and activities from authentic materials and tested them in classes. These materials and activities have been proven to be interesting for secondary school and adult learners. In addition, a simple survey was distributed to eighty-three students. The students’ feedback was gathered, in order to compare and examine if they were more motivated to learn when certain materials they consider interesting—for instance textbooks, handouts and authentic materials—were used in class. The fi